2007
DOI: 10.1576/toag.9.1.021.27292
|View full text |Cite
|
Sign up to set email alerts
|

Dental manifestations of pregnancy

Abstract: Key content Pregnancy has significant effects on the periodontal tissues and pregnancy gingivitis is a common manifestation of this. The host response and oral flora are affected and tooth surface loss and mobility may develop. Further research is required to establish the association between periodontal health and adverse pregnancy outcome. Learning objectives To identify the main dental manifestations of pregnancy. To be able to advise pregnant women on how to maintain good dental health. To be aware o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1
10

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 24 publications
2
28
1
10
Order By: Relevance
“…48,58 Repeated vomiting during pregnancy results in acid-induced erosion, and coupled with the inability to tolerate toothbrushing because of tooth sensitivity and nausea, the oral hygiene of the pregnant woman is severely compromised. 56,59,60 This, along with estrogen-enhanced proliferation and desquamation of the oral mucosa and nutrients provided by the bleeding gingiva creates a suitable environment for an overgrowth of Gram-negative anaerobes in the plaque. [47][48][49][50]61,62 Association of periodontal disease with PTB.…”
Section: Resultsmentioning
confidence: 99%
“…48,58 Repeated vomiting during pregnancy results in acid-induced erosion, and coupled with the inability to tolerate toothbrushing because of tooth sensitivity and nausea, the oral hygiene of the pregnant woman is severely compromised. 56,59,60 This, along with estrogen-enhanced proliferation and desquamation of the oral mucosa and nutrients provided by the bleeding gingiva creates a suitable environment for an overgrowth of Gram-negative anaerobes in the plaque. [47][48][49][50]61,62 Association of periodontal disease with PTB.…”
Section: Resultsmentioning
confidence: 99%
“…(1)(2)(3)(4)(5)(6) However, data on the prevalence of oral lesions in the different trimesters of pregnancy is scarce. Investigations that have been done in the different trimesters are mainly restricted to dental health status and not many factors have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…[102] The palatal surfaces of the upper incisors and canines the most a complaint of sensitivity. [103] On the contrary with lopez et al, 2002, reported a lower prevalence of Periodontal disease of 29.85% in the pregnant Chilean population. [104] Piscoya et al2012, who found that the prevalence of periodontitis was 11%.…”
Section: Discussionmentioning
confidence: 92%